Persepsi Masyarakat Etnis Tionghoa Surabaya Terhadap Acara Pojok Kampung Segmen Blusukan Pecinan Di Jtv Surabaya - Triyanto Triyanto; Ririn Risnawati; Umar Basuki (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
This research aimed to: 1) Find out the content of Blusukan Pecinan on Pojok Kampung Programme segments in JTV Surabaya; 2) Find out Public Perceptions of Tionghoa Ethnic in Kampung Kapasan Dalam Surabaya regarding to the Segment of Blusukan Pecinan in JTV Surabaya. The methodh of this research is descriptive qualitative. The results showed that the content of Segment Blusukan Pecinan in JTV is culture consist of art, tradition, culture and culinary with the percentage 60% Tionghoa’s culinary and 40% general culinary. Relating to the attention factors, functional factors, the perception of the image and complexity message, Tionghoa Ethnic public in Kampung Kapasan Dalam Surabaya perceive the Blusukan Pecinan as good segments, interesting, gives information and insights, and able to keep the culture of Tionghoa Ethnic. The using of three languages in the Blusukan Pecinan Segment Suroboyoan Language, Mandarin and Indonesia as unique thing which characterizes the Segment of Blusukan Pecinan and it should be retained. The suggestions for Blusukan Pecinan Segment is the time and duration of views should be more added so the information more depth.